Real interest rate, exchange rate, inflation rate and economic growth in Malaysia: An ARDL approach - Abu Bakar, Nor Aznin (Global Academic Execellance, 2019)
The purpose of this paper is to examine the relationship between the real interest rate, exchange rate, inflation rate and economic growth in Malaysia with the inclusion of two controlled variables, namely trade openness and FDI. This study uses the time series data for the period of 1985-2017 and employed the ADF test to test for the stationarity of all variables. An autoregressive distributed lag (ARDL) approach is employed to estimate the relationship of independent variables and economic growth. The presence of long-run and short run relationship among variables are revealed with different signs and magnitude. The empirical results show that real effective exchange rate, trade openness and FDI have a positive relationship with the economic growth in the short run. Nevertheless, inflation and real interest rate exhibit negative relationship with the economic growth in the short run. In the long run, real exchange rate and FDI accelerate the economic growth of Malaysia. However, real interest rate causes economic growth to decrease in the long run. Additionally, for the short- run, the value of ECM (-1) is negative, significant and lower than unity which indicates convergence to equilibrium. Based on the results obtained it can be concluded that in the long run, the exchange rate and FDI play a vital role influencing the economic growth of Malaysia, therefore the government needs to revise and implement policies that related to these variables to enhance the economic growth of the economy.